Investigation of serum level relationship anti-glutamic acid decarboxylase antibody and inflammatory cytokines (IL1-β, IL-6) with vitamins D in type 2 diabetes - Pouresmaeil, Vahid; Mashayekhi, Sarmad; Sarafraz Yazdi, Mohammad (Journal of diabetes and metabolic disorders, 2022)
Background Various factors are involved in the development and progression of diabetes mellitus, from cytokines and autoimmune destruction of pancreatic beta cells to vitamin D. This study aimed to investigate the association of serum levels of anti-glutamic acid decarboxylase (anti-GAD) and inflammatory cytokines with vitamin D in type 2 diabetes (T2D). Methods This case-control study was performed on 30 patients with T2D and 30 healthy individuals in Mashhad hospitals in 2020. Lipid profile, creatinine, uric acid, FBS, HbA1c, and blood pressure were recorded. All study variables were measured, particularly serum vitamin D, anti-GAD, and inflammatory cytokine levels in diabetic patients, and the data were compared to those from healthy subjects by performing an appropriate statistical analysis. Results Diabetic patients with a mean age of 52.9 ± 10.4 years, including 16 women and healthy individuals with a mean age of 48.5 ± 10.4 years, including 16 women, were studied. BMI level ( P = 0.002), systolic blood pressure ( P = 0.034), HbA1c, insulin, IL-6, IL1-β, anti-GAD levels, and insulin resistance in diabetic patients were significantly higher than the control group ( P = 0.001). The vitamin D level in the control group was significantly higher than in the case group ( P = 0.0001). The results showed a significant direct relationship between IL-6, IL-1β, and anti-GAD with HbA1c, FBS, insulin, and insulin resistance. However, there was a significant inverse relationship between IL-6, IL-1β, and anti-GAD with vitamin D. Conclusions Inflammatory cytokines and anti-GAD and vitamin D are associated with diabetes, and thus controlling these factors can help improve T2D.